Analysis of phosphorylation sites of protein kinases in Cryptosporidium - Barudin, Mohd Aiman; Md Isa, Muhammad Lokman; Mat Yusof, Afzan (Malaysian Society of Applied Biology, Universiti Kebangsaan Malaysia, 2018)
Cryptosporidiosis is a disease caused by apicomplexan parasite genus Cryptosporidium. In humans, disease manifestation ranges from mild to life threatening condition. Protein kinases are a promising drug target for cryptosporidiosis. Protein kinases act on serine, threonine or tyrosine residues of proteins leading to phosphorylation. In this study, protein sequences of kinases of Cryptosporidium associated with cryptosporidiosis were retrieved and searched from NCBI GenBank database. The phosphorylation potential of protein kinases in this parasite has been evaluated using NetPhos 3.1 Server software. This software is an artificial neural network method that predicts phosphorylation sites in independent sequences with sensitivity and fidelity in the range from 69% to 96%. Phosphorylation potential of amino acid residues of kinases in Cryptosporidium was studied. The results indicate that specific residues of amino acids in kinases have a phosphorylation potential suggesting that these residues are important target sites in protein kinases based anti-cryptosporidial therapy. The study reveals that serine, threonine and tyrosine residues of protein kinases having phosphorylation potential close to 1 could be an important target for anti-Cryptosporidium therapies. Hence, different species of Cryptosporidium can provide important insights into development of anti-Cryptosporidium drug regime using kinase inhibitors.